Transforming the Waste Bank through digitalization technology to improve the community's economy in Makassar City - Ashar, Andi Idham Danal; Yunus, Moh (Universitas Negeri Makassar, 2025)
This research is reviewed from the waste problem has become a crucial issue in various big cities in Indonesia, especially in Makassar City. Seeing the condition of Makassar City which has a vision to become a Smart City but the reality that occurs in the community in general is not accustomed to sorting household waste based on its type (organic, inorganic, B3). Most of the waste is mixed and directly thrown in the trash, this makes the recycling process very difficult, many waste banks that have been formed are no longer active due to lack of assistance, weak management systems and no adequate technological support, there is no integrated digital system starting from collection, recording and reporting of waste volume so that waste bank transactions are still done manually so that they are vulnerable to data loss. The purpose of this study is to identify and analyze the transformation of waste banks through digitalization technology to improve the economy of the community in Makassar City. The research method used is qualitative research using a phenomenological approach that aims to analyze the transformation of waste banks through digitalization technology to improve the economy of the community in Makassar City. Data collection techniques used are observation, interviews and documentation. The technical analysis of research data is based on the theory of Miles and Huberman, namely data reduction, data presentation and drawing conclusions.